2009
DOI: 10.1017/s1755048309000194
|View full text |Cite
|
Sign up to set email alerts
|

The Politics of Muslims in America

Abstract: This article analyzes political participation and the attitudes of Muslim-Americans. Assessing national patterns, the first part highlights several regression models, discerning the impact of race/ethnicity, gender, foreign born status, age, and education on political activity and attitudes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…Gender could also play an important role when assessing the political engagement of Muslims . Wearing the headscarf, or hijab, could expose women to greater scrutiny, and Muslim women may be less involved in politics than men due largely to conservative notions of women's proper role within the household and the community (Jalalzai, ). However, recent empirical studies have not found any significant differences between the political participation of Muslim men and women in the United States (Ayers & Hofstetter, ; Dana, Barreto, & Oskooii, ; Jamal, ).…”
Section: Variable Specification and Descriptive Statisticsmentioning
confidence: 99%
“…Gender could also play an important role when assessing the political engagement of Muslims . Wearing the headscarf, or hijab, could expose women to greater scrutiny, and Muslim women may be less involved in politics than men due largely to conservative notions of women's proper role within the household and the community (Jalalzai, ). However, recent empirical studies have not found any significant differences between the political participation of Muslim men and women in the United States (Ayers & Hofstetter, ; Dana, Barreto, & Oskooii, ; Jamal, ).…”
Section: Variable Specification and Descriptive Statisticsmentioning
confidence: 99%
“…Second, in addition to building on the relative dearth of research American Muslims, this study highlights the disparate ways in which key determinants influence political behavior within this community's subgroups. Whether due to the difficulty in obtaining a sizeable sample from this relatively small population (Patterson, Gasim, and Choi 2011; Djupe and Calfano 2012), 2 or simply an implicit decision to limit the analysis to inferences about the sample as a whole (Ayers and Hofstetter 2008; Jalalzai 2009), studies of American Muslim political attitudes and behavior conditioned on key demographic distinctions is, not surprisingly, quite rare (see below for exceptions to this general rule). Altogether absent, however, is a comprehensive assessment of the differential effects attendant to these distinctions.…”
mentioning
confidence: 99%
“…Available studies of Muslim Americans, though few in number, produce results similar to those among non-U.S. Muslims. In studies that include statistical controls for religiosity, high levels of education and income tend to foster more secular, progressive attitudes (Baker and Jamal 2009:155-56), greater religious tolerance (Djupe and Calfano 2012a), and even declining fertility rates (Kulczycki and Lobo 2001), while also channeling energy toward greater political participation (Jalalzai 2009).…”
Section: Discussionmentioning
confidence: 99%